Development of Regional and Sectoral Economy in the Context of Digitalization, in Particular, the Formation and Development of Modernized Banking Businesses (Eurasian Scientific Herald, 2022)
Digitalization affects all sectors of the economy of states and regions. Naturally, digitalization also has an impact on the banking sector of the regions. Modernization of banks is an integral part of the development of the digital economy. This article identifies the prospects and threats of the formation of a new model of banking business, focused on the transformation of the bank into an integrator of values in the digital space.